2016
DOI: 10.1002/cncr.30460
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of equivocal human epidermal growth factor receptor 2 results and clinical utility of alternative chromosome 17 genes in patients with invasive breast cancer: A cohort study

Abstract: Summary Background The 2013 testing guidelines for determining HER2 status included new cutoff points for HER2/CEP17 ratio and average HER2 copy number/cell and recommended using a reflex test with alternative chromosome 17 probes (Ch17P) to resolve equivocal HER2 results. We sought to determine the clinical utility of alternative Ch17P in equivocal cases and the effect of equivocal results and/or the change in HER2 status on patients’ outcome. Methods Our institution’s database of HER2 dual-probe fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 36 publications
4
22
0
Order By: Relevance
“…To date, there is no published data demonstrating that patients who are HER2 positive solely on the basis of alternative probe FISH will respond to anti‐HER2 therapy similarly to patients who are positive by conventional assays. A recent study of patients with Stage I‐III breast cancer, who were not treated with anti‐HER2 therapy, showed no difference in survival between patients with HER2 equivocal breast cancer vs HER2 nonamplified cases, as well as no difference in survival between HER2 equivocal cases which were converted to HER2‐positive status based on alternative probe HER2 FISH results . While this study used a different set of alternative probes (RARA and SMS) compared to our investigation, they observed a similar positive conversion rate (61%) using alternative probe HER2 FISH …”
Section: Resultssupporting
confidence: 61%
“…To date, there is no published data demonstrating that patients who are HER2 positive solely on the basis of alternative probe FISH will respond to anti‐HER2 therapy similarly to patients who are positive by conventional assays. A recent study of patients with Stage I‐III breast cancer, who were not treated with anti‐HER2 therapy, showed no difference in survival between patients with HER2 equivocal breast cancer vs HER2 nonamplified cases, as well as no difference in survival between HER2 equivocal cases which were converted to HER2‐positive status based on alternative probe HER2 FISH results . While this study used a different set of alternative probes (RARA and SMS) compared to our investigation, they observed a similar positive conversion rate (61%) using alternative probe HER2 FISH …”
Section: Resultssupporting
confidence: 61%
“…We identified genomic regions of chromosome 17 reported as alternative control sites for assessment of HER2 FISH ratios. 19 , 20 , 21 These sites were assessed in METABRIC for copy number gains and losses relative to ERBB2/HER2 gains and losses ( Table 1 ) ( Figure 2 ) (eFigure 1 in the Supplement ).…”
Section: Resultsmentioning
confidence: 99%
“…The second part involved reassessment of HER2 status in breast cancers from women accrued to BCIRG-005 (ClinicalTrials.gov Identifier NCT00312208 ) whose cancers had HER2 -to-CEP17 FISH ratios of less than 2.0 and an average of 4.0 to 5.99 HER2 genes per tumor cell (ISH-equivocal) or cancers with FISH ratios of less than 2.0 and average HER2 gene copies less than 4.0 per tumor cell (ISH-negative) using alternative control probes to reassess HER2 status, according to the 2013/2014 ASCO-CAP guidelines. 19 , 20 , 22 , 26 Finally, we assessed clinical outcomes in these subgroups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the 2013 ASCO/CAP guideline recommended to repeat HER2 testing using an alternative probe for CEP17 or for another gene in chromosome 17 not expected to co-amplify with HER2 for the ISH equivocal cases (now ISH group 4 in the updated 2018 ASCO/CAP guideline) [12,26]. However, following studies have shown that with alternative probes, HER2 ISH equivocal cases were upgraded to HER2 ISH positive status in a significant proportion, and clinicopathologic features of those upgraded cases were not compatible with those of HER2-amplified breast cancers, suggesting that use of alternative probe is not reliable in clinical practice [32,47]. The updated 2018 ASCO/ CAP guidelines do not recommend the use of alternative probe as standard practice due to limited evidence on its analytical and clinical validity [13].…”
Section: Suggestionsmentioning
confidence: 99%